Using digital images to evaluate the colorimetric response of lisianthus plants to nutrient solutions in hydroponic systems - Rodríguez-Serrano, Daniela; Lara-Viveros, Francisco Marcelo; Sánchez-Herrera, Susana Graciela; Aguado-Rodríguez, Graciano Javier (REVISTA TERRA LATINOAMERICANA, 2020)
Lisianthus is an ornamental plant that has recently acquired great importance in national and international markets for its beauty and color variety. This crop is traditionally established in soil, but little information is known regarding its growth and development habits in hydroponic systems. Therefore, the objective of this study was to evaluate through digital images the change in leaf and flower colors in lisianthus cultivation in hydroponics with different nutrition solutions. Four nutrition solutions (NS) were tested in the cultivation stage: (NS1) Steiner solution as control group and the rest of the treatments were modified solutions; (NS2) double concentration of Steiner solution; (NS3) a high amount of K was added; and (NS4) higher amount of calcium (18 mEq L-1). The parameters evaluated were plant height and leaf number, obtaining significant differences in both NS1 with respect to the NS4 leaf and flower phenotypic characteristics by the intensity of red, blue, and green (RGB) color model values; leaf was not affected by the treatments with modifications made to the Steiner solution. The variable R only showed significant differences in NS1 compared to NS4 with a higher amount of calcium, but it did not occur for the other variables. This phenomenon only occurred on day 61 after transplant (DAT). Regarding the effect of the nutrient solution on flower color, a significant difference was found in the R variables in Steiner solution (NS1). A difference was also observed in the solution with high potassium concentrations. The same occurred for the artificial variables used.